Wireless Data Communications in WSN Networks Using UAV - Miptahudin, Rd Apip; Suryani, Titiek; Wirawan, Wirawan (Society of Visual Informatics, 2025)
This research explores the impact of environmental and technical factors on air-to-ground (A2G) wireless communications using drones, specifically tackling challenges like multipath propagation, Doppler effects, and geographical variability. The study aims to analyze performance determinants of A2G communications, develop a simulation model to predict communication issues and offer recommendations for optimizing interactions between drones and ground stations. The methodology includes data collection from field tests and simulations, focusing on various environmental and weather conditions. Statistical data analysis, including regression and hypothesis testing, is employed to interpret the results. Key findings reveal that factors such as operational altitude, drone speed, and weather conditions—mainly rain—significantly affect throughput, latency, and packet loss. Optimal communication performance is achieved at a drone height of 120 meters, with rural environments offering the best conditions for data transmission. Conversely, urban settings experience decreased throughput and increased latency due to physical obstructions like buildings and infrastructure. These insights highlight the need for adaptive communication technologies and comprehensive testing across diverse conditions. The research advocates further exploring advanced antenna technologies, dynamic operational adjustments informed by real-time environmental data, and robust security measures to enhance communication reliability. In conclusion, this study establishes a strong foundation for future advancements in drone communication technologies, aiming to improve the safety and efficiency of drone operations across various applications. The findings serve as a roadmap for developing innovative solutions to address the inherent challenges of A2G communications in varying operational environments.